Investigation of irregularity of flow distribution across the tube bundle in shell-and-tube heat exchanger with segmental baffles using PIV method - Ligus Grzegorz; Kołodziej Szymon (E3S Web of Conferences, 2017)
This paper presents the results of an experimental study into flow through a tube bundle applied in shell-and-tube heat exchanger with segmental baffles built on an industrial scale. The reported research applied Digital Particle Image Velocimetry (PIV) technique. The study offered the determination of the velocity vector fields, which were subsequently used for identification and measurement of irregularity of flow distribution across the tube bundle. Differences in the intensity of local flow velocities in shell side were identified by velocity profiles analysis. Furthermore correlation between the map of local velocity and its location in particular tube rows was described. As a result, the three main regions of flow velocity variation throughout cross-section of the shell side were identified.